6+2w=42

Simple and best practice solution for 6+2w=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2w=42 equation:


Simplifying
6 + 2w = 42

Solving
6 + 2w = 42

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2w = 42 + -6

Combine like terms: 6 + -6 = 0
0 + 2w = 42 + -6
2w = 42 + -6

Combine like terms: 42 + -6 = 36
2w = 36

Divide each side by '2'.
w = 18

Simplifying
w = 18

See similar equations:

| z^2-z-20=0 | | x^2+11x-28=0 | | 20=c(c-8) | | 7y+-2x=5 | | 14s^2-33s+18=0 | | 4a^2+15-16a=0 | | 72=-8(4x-5) | | 4b^2-2=322 | | 5m=13 | | 8x^2-3x+2=7x^2 | | 7x+-2y=5 | | 500=9w+2l | | 5-3x=5x-11 | | z^4-37z^2+36=0 | | x-8=4-x | | 42y^2-69y+20=7y^2-8 | | 120=5l+2w | | 20t^2-39t+18=0 | | 6c-9c+14=20 | | -9x+2=-8x-1 | | 2x^2-17x+27=0 | | (x-5)(x+5)=24 | | (5v-1)(6-v)=0 | | 4x^4=65x^2-196 | | 6x^3-2x^2+19=0 | | 2r^3-6r^2=56r | | 6d+11+3d=47 | | x^7-7x=0 | | x^2+11x-27=0 | | 3p-20=-29+2p | | 80+.50x=180 | | v^2-4=0 |

Equations solver categories